Visibility and Effectiveness of PJOK Learning in High Schools in Buleleng District - I Made Subawa Putra Loka; I Ketut Yoda; I Gede Suwiwa (Universitas Pendidikan Ganesha, 2024)
Sports and health physical education involves physical activity for students which aims to improve fitness, healthy living behavior and foster sportsmanship. The aim of this research was to determine the visibility and effectiveness of PJOK learning in senior secondary schools (SMA) throughout Buleleng Regency. This type of research is descriptive - quantitative with a sample of 23 schools from a population of 30 schools. By using data collection methods using surveys, observations, documentation studies, interviews and questionnaires. The results of this research show two results in terms of visibility and effectiveness of learning. In terms of visibility, the teacher's personality competency score is 7.66 in the